Komplementaritas dalam Praktik: Relasi Politik-Administrasi dalam Tata Kelola Infrastruktur Jalan di Kabupaten Wonosobo - Tirta Pandu Winata; Sujatmiko Sujatmiko; Yuni Kurniasih (Journal of Education on Social Science (JESS), 2025)
This research aims to analyze and explain the dynamics of complementarity politics and administration in the relationship between democracy and bureaucracy in the road infrastructure governance process in Wonosobo Regency. This phenomenon is interesting to study because it involves political actors in the Regional Legislative Council (DPRD), as well as administrative actors from the Regional Development Planning Agency (Bappeda) and the Public Works and Spatial Planning Agency (Dinas PUPR) in Wonosobo Regency, all engaged in a complementary relationship regarding road infrastructure issues, an issue that has garnered significant attention from the community. The complementarity framework used in this study refers to the framework proposed by Svara (2001), which is based on three principles: interdependency, reciprocal influence, and extensive interaction. This study employs a qualitative method with a case study approach. The results indicate that efforts are being made to preserve democracy while avoiding subordination by Bappeda and the PUPR agency to DPRD control; there is an integral relationship between the DPRD, Bappeda, and the PUPR agency in maintaining public preferences regarding road infrastructure; parliamentary involvement in the inclusiveness of the administrative process; and other factors in the planning process for road infrastructure development in Wonosobo Regency.